The Influence of Reflective Journals on Critical Thinking Ability of Students - Penggabean, Meicky Shoreamanis; Cendana, Wiputra; Ani, Yubali (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aimed to analyze the effect of reflective journals on students’ critical thinking skills. The research subjects were 30 students majoring in Teacher Education at the Elementary School, Faculty of Education, Private University of Tangerang—data collection using a questionnaire and student reflection writing. The data obtained is processed qualitatively. This study analyses the skill aspect of critical thinking using skills indicators of critical thinking according to Facione, namely interpretation, analysis, evaluation, conclusion, explanation, and self-regulation. The study results show that knowing note-taking methods can help students make journals from the courses they teach. This helps students think critically about each course and learn the nature of the course and note-taking methods appropriate to the course. Meanwhile, based on the research findings, it is known that Cornell Notes, Mapping Method, Charting Method, Sentence Method, and Visual Note Taking are methods appropriate to the courses taught by students. Thus it can be concluded that reflective journals influence students’ critical thinking skills.